2021
DOI: 10.1002/vms3.664
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and antimicrobial resistance of Escherichia coli in broiler chickens, farmworkers, and farm sewage in Bangladesh

Abstract: Background: Antimicrobial resistance (AMR) has become an emerging threat worldwide, and developing countries such as Bangladesh are considered to be at greater risk of disseminating the resistant bacteria between human-animal interfaces.Objectives: The present study was carried out to determine the prevalence and AMR profile of Escherichia coli isolated from broiler chickens, the environment, and farmworkers. This study also aimed to identify the risk factors associated with multidrugresistant (MDR) E. coli in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 48 publications
1
9
1
1
Order By: Relevance
“…According to the findings of the current survey, the majority of poultry feed and chick dealers have no professional degrees in the veterinary sector, but they recommend antibiotics to farmers based on their experience (usually 3–10 years). One of the main issues that could encourage the overuse of antibiotics in veterinary and human medicine in Bangladesh and several other developing nations is the over-the-counter sale of antibiotics [ 3 , [21] , [22] , [23] ]. In the current survey, we also found that poor farmers were obtruded by dealers/local agents to sell their live birds to them, as the farmers received DOCs, feed, medicines, and other necessary inputs as loans.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of the current survey, the majority of poultry feed and chick dealers have no professional degrees in the veterinary sector, but they recommend antibiotics to farmers based on their experience (usually 3–10 years). One of the main issues that could encourage the overuse of antibiotics in veterinary and human medicine in Bangladesh and several other developing nations is the over-the-counter sale of antibiotics [ 3 , [21] , [22] , [23] ]. In the current survey, we also found that poor farmers were obtruded by dealers/local agents to sell their live birds to them, as the farmers received DOCs, feed, medicines, and other necessary inputs as loans.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the prevalence in the environmental samples was 31.3, 40, and 100%, respectively, and 28.6, 25, and 0 from worker's hands. In a parallel investigation, Mandal et al (2022) recovered 114 E. coli isolates from 150 examined samples (76%). However, in comparison to the findings of our investigation, the higher prevalence that was reported could be ascribed to the sample types, as such work comprised cloacal swabs, hand-washed water, and farm sewage samples.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that tetracyclines, quinolones, and neomycin exhibited the highest rates of resistance, with tetracyclines, ampicillin, and nalidixic acid showing the highest rates of resistance in poultry strains. These findings are consistent with previous studies that have established a link between antibiotic use and bacterial resistance in E. coli [ 22 ].The prevalence of antimicrobial resistance among fecal E. coli isolates may be attributed to the transmission of resistant bacteria or resistance plasmids from poultry to poultry workers [ 23 ]. The selection of antimicrobial resistance in bacteria is primarily attributable to the misuse of antibiotics, overcrowding, and poor sanitation practices in poultry farms [ 24 ].…”
Section: Discussionmentioning
confidence: 99%